Effect of ultrasonication on synthesis of forsterite ceramics - Sara Lee K.Y.; Christopher Chin K.M.; Ramesh S.; Tan C.Y.; Hassan M.A.; Purbolaksono J.; Teng W.D.; Sopyan I. (2023)
The current study is to examine the effect of ultrasonication on the synthesis of forsterite (Mg2SiO4) powder. Ultrasonication and ball milling were performed using talc and magnesium oxide as starting precursors, followed by heat treatment to obtain forsterite. The X-ray diffraction results of the powders heat treated at 1200 C showed that the 2 hours ultrasonication followed by 3 hours ball milling was beneficial in retaining the forsterite phase in the matrix. The results were similar to ball milling for 10 hours prior to heat treatment. The derived powders also exhibited very fine crystallite size in the range of 28 to 35 nm thus indicating the viability of using ultrasonication as part of the processing steps in the synthesizing of forsterite ceramics. (2012) Trans Tech Publications, Switzerland.